Figure 7 in Recent evolution of ancient Arctic leech relatives: systematics of Acanthobdellida ... - Carle, Danielle Božena De; Gajda, Łukasz; Bielecki, Aleksander; Cios, Stanisław; Cichocka, Joanna M.; Golden, Heidi E.; Gryska, Andrew D.; Sokolov, Sergey; Shedko, Marina Borisowna; Knudsen, Rune; Utevsky, Serge; Świątek, Piotr; et al. (Zenodo, 2022)
Figure 7. Scanning electron micrographs of the anterior body region. A, B, small specimens of Acanthobdella peledina (5 mm; Sweden; A) and Paracanthobdella livanowi (3.5 mm; B). C, D, large specimens of A. peledina (12 mm; Norway; C) and P. livanowi (11 mm; Kamchatka; D). In the large P. livanowi specimen, body segmentation and chaetae in the anterior sucker are barely visible. Arrow, mouth opening; Arabic numerals 1–5 indicate rows of chaetae; d, deepening between pairs of chaetae. ... : Published as part of Carle, Danielle Božena De, Gajda, Łukasz, Bielecki, Aleksander, Cios, Stanisław, Cichocka, Joanna M., Golden, Heidi E., Gryska, Andrew D., Sokolov, Sergey, Shedko, Marina Borisowna, Knudsen, Rune, Utevsky, Serge, Świątek, Piotr & Tessler, Michael, 2022, Recent evolution of ancient Arctic leech relatives: systematics of Acanthobdellida, pp. 149-168 in Zoological Journal of the Linnean Society 196 on page 162, DOI: 10.1093/zoolinnean/zlac006, http://zenodo.org/record/7037718 ...